2021
DOI: 10.1016/j.ijid.2021.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Social media for field epidemiologists (#SoMe4epi): How to use Twitter during the #COVID19 pandemic

Abstract: Social media for field epidemiologists (#SoMe4epis): How to use Twitter during the #COVID19 pandemicIn line with the topic of this article, we use hashtags (#) and Twitter accounts (@) throughout the text where available and appropriate. We invite readers to check out these hashtags and accounts, which we have found to be some of the most informative and engaging in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The COVID-19 pandemic hit Germany at the beginning of 2020. General information in Germany has been delivered on Twitter, with authorities, and particularly other experts such as scientists, science communicators, politicians, and journalists, distributing COVID-19–related tweets [ 2 ] and content on the German Twitter network. Both authorities and COVID-19 experts use Twitter to directly share their own insights and opinions with the Twitter community in an unfiltered manner independent of traditional media.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic hit Germany at the beginning of 2020. General information in Germany has been delivered on Twitter, with authorities, and particularly other experts such as scientists, science communicators, politicians, and journalists, distributing COVID-19–related tweets [ 2 ] and content on the German Twitter network. Both authorities and COVID-19 experts use Twitter to directly share their own insights and opinions with the Twitter community in an unfiltered manner independent of traditional media.…”
Section: Introductionmentioning
confidence: 99%
“…Learning processes which were attached to gaining health information were highly based on the social contexts (Sbaffi and Rowley, 2017;Vega et al, 2011). Therefore, Twitter can be a key tool to share experiences among COVID-19 (Hammer et al, 2021). This could be the component that differentiates the results from previous studies for Turkey's situation.…”
Section: Discussionmentioning
confidence: 99%
“…, 2011). Therefore, Twitter can be a key tool to share experiences among COVID-19 (Hammer et al , 2021). This could be the component that differentiates the results from previous studies for Turkey’s situation.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that followers' engagement increases on social media if the brand content is linked to concepts such as happiness and health and safety [60]. "Social media have been developed rapidly and it is recognized as a key strategic element of organizations competitiveness and survival" [61], and its value is recognized in various fields [62][63][64], being related to happiness and consumption habits [65]. The marketing options provided by Social Media to professionals elongate the modus operandi of dentists to promote their advice, practices and clinics [42,[66][67][68].…”
Section: Smm and The Personalisation Conceptmentioning
confidence: 99%